Prediction of shear crack width for steel fiber reinforced concrete beams. (8th March 2022) - Negi, Bichitra Singh; Jain, Kranti
Abstract: The shear crack width, crack behavior, and crack development of 24 reinforced concrete beams have been experimentally investigated. All the beams reinforced with longitudinal reinforcement and hooked‐end steel fibers in place of transverse reinforcement. Hooked‐end steel fibers 35 and 60 mm long are used at volume fractions ranging from 0.75% to 1.5% in the first case, and from 0.5% to 1% in the latter case. For extending the scope of the investigation, two types of concrete matrices (normal‐strength of 25 MPa and medium‐strength of 45 MPa) have been investigated. A simple mechanics‐based mathematical model is developed by determining the strains in the transverse direction of shear cracks and the average horizontal spacing between the shear cracks. The accuracy of the model has been confirmed with the experimental results and conservative predictions have been observed with mean, SD, and coefficient of variation as 0.99, 0.19, and 18.96, respectively. Based on detailed mathematical and experimental investigation, the minimum approximately observed shear crack width has value of 0.4 mm for all SFRC beams therefore the allowable shear crack width of 0.4 mm, for steel fiber reinforced concrete has been recommended.